Microvascular assessment of fascio-cutaneous flaps by ultrasound: A large animal study - Goudot, Guillaume; Berkane, Yanis; de Clermont-Tonnerre, Eloi; Guinier, Claire; Filz von Reiterdank, Irina; van Kampen, Antonia; Uygun, Korkut; Cetrulo, Curtis L.; Uygun, Basak E.; Dua, Anahita; Lellouch, Alexandre G. (Frontiers in Physiology, 2022)
Objectives: Blood perfusion quality of a flap is the main prognostic factor for success. Microvascular evaluation remains mostly inaccessible. We aimed to evaluate the microflow imaging mode, MV-Flow, in assessing flap microvascularization in a pig model of the fascio-cutaneous flap. Methods: On five pigs, bilateral saphenous fascio-cutaneous flaps were procured on the superficial femoral vessels. A conventional ultrasound evaluation in pulsed Doppler and color Doppler was conducted on the ten flaps allowing for the calculation of the saphenous artery flow rate. The MV-Flow mode was then applied: for qualitative analysis, with identification of saphenous artery collaterals; then quantitative, with repeated measurements of the Vascularity Index (VI), percentage of microvessel detection per 2D ultrasound view area. The measurements were then repeated after increasing arterial flow by clamping the distal femoral artery. Results: The MV-Flow mode allowed a better follow-up of the saphenous artery's collaterals and detected microflows not seen with the color Doppler. The VI was correlated to the saphenous artery flow rate (Spearman rho of 0.64; p= 0.002) and allowed to monitor the flap perfusion variations. Conclusion: Ultrasound imaging of microvascularization by MV-Flow mode and its quantification by VI provides valuable information in evaluating the microvascularization of flaps.